(untitled) (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Obsessive-compulsive disorder (OCD) is a chronic psychiatric condition characterized by intrusive thoughts (obsessions) and repetitive behaviors (compulsions), leading to significant distress. Selective serotonin reuptake inhibitors (SSRIs) such as Fluoxetine and Sertraline are the primary pharmacological treatments for OCD. However, comparative studies on their efficacy and tolerability remain limited. Objective: This study aimed to evaluate the effectiveness and tolerability of Fluoxetine versus Sertraline in OCD patients. Methods: This longitudinal analytical study was conducted at Dhaka Medical College, Bangladesh, from January to December 2022. A total of 232 OCD patients, diagnosed based on DSM-5 criteria, were recruited from the Department of Psychiatry. Participants were divided into two groups: Group A (n = 116) received Fluoxetine, and Group B (n = 116) received Sertraline for three months. Symptom severity was assessed using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), and data were analyzed using SPSS version 25. Results: Both medications significantly reduced Y-BOCS scores (p = 0.000); however, Fluoxetine demonstrated superior efficacy. After three months, Fluoxetine-treated patients showed greater symptom reduction (8.52 ± 2.15 vs. 10.1 ± 3.58, p = 0.000). Recovery rates were higher in the Fluoxetine group (60.42% vs. 39.58%), though not statistically significant. Fluoxetine had better tolerability, with dry mouth (30.1%) being the most common side effect, whereas Sertraline was associated with higher agitation (34.7%) and hallucinations (28.7%). Conclusion: Fluoxetine showed greater efficacy and better tolerability than Sertraline, making it a preferred treatment option for OCD. Further studies with larger samples are recommended. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 46-51